Peniadaan Salat Jumat dalam Surat Edaran Gubernur Sulsel Nomor: 451.11/2057/2020 Selama Pandemi Covid-19 Perspektif MaqÄá¹£id al-SyarÄ«ah - Sirajuddin, Sirajuddin; Kasjim Salenda; Abdul Wahid Haddade (Pusat Penelitian dan Pengabdian Masyarakat (P3M) Sekolah Tinggi Ilmu Islam dan Bahasa Arab (STIBA) Makassar, 2020)
This research aimed to analyze the relevance of dismissal of friday prayers in circular letter of south sulawesi governor number: 451.11 / 2057/2020 during covid-19 pandemic from the perspective of maqÄá¹£id al-syarÄ«â€™ah. This research is library research using a qualitative approach and content analysis techniques. The results of the research conclude that the substance of the circular letter is relevant to the principle of maqÄá¹£id al-syarÄ«â€™ah which is the core philosophy of the formation of Islamic law in presenting the benefit of mankind in the world and the hereafter, both from the aspect of maqÄá¹£id al-kulliyyah (universal) and maqÄá¹£id al-juz'iyyah (partial) especially maqÄá¹£id in obeying a leader. Therefore, the emergence of the phenomenon of counter attitudes from some people and even preachers towards the policy should not occur.